1973
DOI: 10.1084/jem.138.5.1194
|View full text |Cite
|
Sign up to set email alerts
|

Function of Macrophages in Antigen Recognition by Guinea Pig T Lymphocytes

Abstract: Antigen activation of DNA synthesis in immune thymus-derived lymphocytes of guinea pigs requires the cooperation of macrophages and lymphocytes. We have investigated the role of histocompatibility determinants in this macrophage-lymphocyte interaction using cells from inbred strain 2 and 13 guinea pigs. The data demonstrate that efficient presentation of macrophage-associated antigen to the lymphocyte requires identity between macrophage and lymphocyte at some portion of the major histocompatibility complex. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
129
0
1

Year Published

1977
1977
1997
1997

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 954 publications
(136 citation statements)
references
References 31 publications
6
129
0
1
Order By: Relevance
“…Class I1 MHC molecules are required for antigen presentation to T helper cells (36), for cytolytic T cell induction (37), and for stimulation of autologous and allogeneic mixed lymphocyte reactions (38). Other functions of class I1 MHC antigens include selection of mature class II-restricted CD4+ T lymphocytes in the thymus, class I1 MHC-incompatible graft rejection, and transmembrane signaling due to the activation of Iaexpressing cells (39).…”
Section: Discussionmentioning
confidence: 99%
“…Class I1 MHC molecules are required for antigen presentation to T helper cells (36), for cytolytic T cell induction (37), and for stimulation of autologous and allogeneic mixed lymphocyte reactions (38). Other functions of class I1 MHC antigens include selection of mature class II-restricted CD4+ T lymphocytes in the thymus, class I1 MHC-incompatible graft rejection, and transmembrane signaling due to the activation of Iaexpressing cells (39).…”
Section: Discussionmentioning
confidence: 99%
“…Apparently, these cells readily pinocytize/phagocytize this material and present it to the surrounding T cells. It is very likely that either efficient antigen processing occurs in monocytes (3940) andor additional signals are provided by these cells (41), which then stimulate the T cell repertoire that is reactive against chondrocyte membranes in patients with RA. Indeed, clonal analysis demonstrated that there was a high precursor frequency in RA T cells reactive with chondrocyte antigens.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in the guinea pig (1,2) have demonstrated the requirement for genetic identity at the MHC in order for peritoneal exudate cells to present antigen effectively to primed T lymphocytes. Experiments designed to test whether similar genetic restrictions applied to antigen presentation by murine spleen cells are shown in Table I.…”
Section: Antigen Presentation By Syngeneic Semisyngeneic or Allogenmentioning
confidence: 99%